Student Financing of Undergraduate Education 1999-2000. Statistical Analysis Report. Executive Summary - Berkner, Lutz.; Berker, Ali; Rooney, Kathryn; Peter, Katharin; National Center for Education Statistics (ED), Washington, DC.; MPR Associates, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2002)
During the 1999-2000 academic year, about 16.5 million undergraduates were enrolled in postsecondary institutions for all or part of the year as full- or part-time students. More than one-half of them received some type of financial aid from federal, state, institutional, or other sources to meet their educational expenses, receiving, on average, $6,200. This report describes the financing of undergraduate education by students who were enrolled in U.S. postsecondary institutions during the 1999-2000 academic year. It is based on data from the National Postsecondary Student Aid Study (NPSAS:2000), the fifth in a series of surveys conducted by the National Center for Education Statistics. In 1999-2000, 44% of all undergraduates received grants, for an average of $3,500. Twenty-nine percent of all undergraduates received student loans, averaging $5,100. In addition, 5% of all undergraduates held work-study jobs, and 7% received other types of aid. Many undergraduates received more than one type of aid. More undergraduates received grants from federal financial aid programs than from any other single source, but states, postsecondary institutions, and private organizations were also important sources of grant aid to undergraduates. (SLD)
Availability: ED Pubs, P.O. Box 1398, Jessup, MD 20794-1398.Tel: 877-433-7827 (Toll Free); Fax: 301-470-1244; e-mail: edpubs@inet.ed.gov. For full text: http://nces.ed.gov/pubsearch/pubsinfo.asp?pubid=2002167.
ERIC Note: Project Officer, Andrew G. Malizio. For a report on the 1995-1996 academic year, see ED 424 835.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Higher Education; National Surveys; Paying for College; Student Costs; Student Financial Aid; Student Loan Programs; Tables (Data); Undergraduate Students; National Postsecondary Student Aid Study; Numerical/Quantitative Data; Reports, Evaluative